Stability assessment of high-bandwidth DC voltage controllers in single-phase active-front-ends: LTI vs LTP models - Salis, Valerio; Costabeber, Alessando; Cox, Stephen M.; Formentini, Andrea; Zanchetta, Pericle (IEEE, 2018)
In recent years, a considerable effort has been made to minimise the size of DC-link capacitors in single-phase activefront-ends (SP-AFE), to reduce cost and to increase power density. As a result of the lower energy storage, a high-bandwidth outer DC voltage control loop is required to respond to fast load changes. Linearised modelling is usually performed according to the power-balance method and the control is designed using LTI techniques. This is done assuming negligible voltage ripple at twice the grid frequency, and the model is considered valid up to the grid frequency. However, its precise validity limits are usually unknown and the control design becomes empirical when approaching these boundaries. To overcome this drawback, Linear Time Periodic (LTP) theory can be exploited, defining the range of validity of the LTI model and providing precise stability boundaries for the DC-link voltage loop. The main result is that LTP models more accurately describe the system behaviour and provide superior results compared to the LTI ones. Theoretical analysis, simulations and extensive experimental tests on a 10 kW converter are presented to validate the claims.